Empowering Coastal Communities for Sustainable Marine Conservation: Integrating Education, Technology, and Local Engagement in Negeri Mamala - Patrisius Rahabav; Rudolf Kempa; Beatrix Tomasila; Sarlota Singerin; Desembra Sohilait; Sumarni Rumfot; Estin Indria Maahury; Vando Kristi Makaruku; Nandalita Nunuela; Paul Arjanto; Matusela Kunu; Salim Nussy; Fenty Retraubun; Wa Ode Ramliani; Ujian Mahulauw; Meilan Refwutu; Rahmawati Latukau; Yuliana Wakim (CV. TOTUS TUUS, 2025)
Indonesia, as the world's largest archipelagic country, holds a critical position in global marine biodiversity, encompassing over 17,000 islands within the Coral Triangle, known as the epicenter of marine diversity. This region supports extensive ecosystems that are vital for ecological balance, economic stability, and the well-being of millions of people. However, these ecosystems face severe threats from overfishing, plastic pollution, and climate change, which collectively endanger marine biodiversity and disrupt coastal livelihoods. This community service program, conducted by the Educational Administration Study Program at the Faculty of Teacher Training and Education, Universitas Pattimura, aimed to strengthen community awareness and enhance administrative capacity for sustainable marine conservation in Negeri Mamala. The program incorporated educational sessions, digital technology, and hands-on community engagement to address critical marine conservation challenges. Key activities included awareness building, community training, and the integration of immersive technologies like Augmented Reality (AR) and Virtual Reality (VR) to improve participant understanding and retention. The results demonstrated significant improvements in community awareness, administrative skills, and active participation in conservation efforts, aligning with the principles of community-based conservation. This initiative provides a promising model for other coastal communities, highlighting the potential of integrating education, technology, and local engagement to achieve long-term sustainability in marine conservation. Moving forward, continued support, strategic partnerships, and ongoing capacity building will be essential for maintaining and expanding these positive impacts.